(untitled) (Fiep Bulletin - online, 2013)
This objective article to socialize knowledge articulated around the phenomenon of the ludicidade in the critical and creative game of the life of teacher-researchers in corporality. One is about a study that takes care of the requirements of a philosophical reflection: the radicalidade, severe and of adjacent, developed around the thematic ones of the playful one, the game, the aesthetic one and the corporality. The partners are two teacher-researchers in corporality (a man and a woman), that they have the initial formation in Physical Education, chosen for the sensible look of the researcher. In synthesis of the conclusion we can affirm that the phenomenon of the payful in the life of the teacher is a reality that appears for the presence of the game of the corporality in the interlacement of the rational and the sensible one, provoking desregrados jumps of emotions and feelings that if they become dances, gestures and actions that stimulate expressivas attitudes in daily making. The phenomenon of the playful in the life of the teacher shows in its concretude as a work of art, a beautiful picture that if express in alive colors in the beauty of the ocean of sensibilidades, joining life and form, sensitivity and reason, necessity and freedom. The present sensible dimension in life of each one of the teacher, allows to interpret and to intervine of interactive form in the construction of its proper knowledge and in the dynamics of the construction of the knowledge of its pupils. Life histories had demonstrated that the processes of academic formation that had had had implied in a personal investment, exempt and creative that if express today in a professional identity of recognition for its pairs. For the ludicidade it was possible to disclose facetas of “learning to be and to learn to coexist” of these teacher, to be playful before the life. To be playful I obtain same is reflected in the intrapessoal dimension, to be playful with the other express in the interpersonal dimension and to be playful in the challenges and the confrontations of the life shows in the existencial dimension.